Pengaruh Strategi Manajemen Sumber Daya Manusia terhadap Kinerja Guru di MTs Laboratorium UIN Bukittinggi - novelantikavela, novelan; Sesmiarni, Zulfani (UIN Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the effect of human resource management (HRM) strategies on teacher performance at MTs Laboratorium UIN Bukittinggi. A quantitative method with a causal associative approach was employed. Data were collected through a closed-ended questionnaire distributed to 11 full-time teachers, consisting of 25 items. Simple linear regression analysis revealed that HRM strategies significantly influence teacher performance, with a coefficient of determination (R²) of 0.68. The findings indicate that HRM practices such as selective recruitment, continuous training, systematic performance evaluation, and appropriate compensation positively contribute to improvements in teacher discipline, pedagogical competence, and professionalism. Hence, well-structured and targeted HRM is a crucial factor in enhancing teacher performance and educational quality in Islamic junior high schools.